Effect of Oxidative Stress and Fatty Acids Disbalance on the Development of Apoptosis in the Placenta with Cytomegalovirus Infection in the First Trimester - N. A. Ishutina (Scientific Сentre for Family Health and Human Reproduction Problems, 2019)
Background. Reactivation of cytomegalovirus infection (CMV) during pregnancy is associated with manifestation of oxidative stress, both in the maternal peripheral blood and in the placental tissues. One of the effects of oxidative stress is a disturbance of the metabolism of fatty acids, which leads to the initiation of the apoptotic cascade, the death of trophoblast cells and, as a result, tissue or organ dysfunction, promoting to the development of a pathological condition. However, an analysis of the current literature indicates insufficient information on this problem in the villous chorion of the placenta in CMV infection.Aims. To study the relationship between the oxidative stress development and fatty acid imbalance in apoptosis of trophoblast cells during reactivation of CMV in the first trimester.Material and methods. We examined peripheral blood, urine, a homogenate of the villous chorions from 35 pregnant women with CMV reactivation within 9–11 weeks of pregnancy and from 30 pregnant women without CMV of the same gestation period. We studied levels of IgM and IgG for cytomegalovirus, low-avid IgG antibodies to cytomegalovirus (avidity index), phospholipase A2 content, fatty acid content, number of apoptotic trophoblast cells, fatty acid peroxide content and catalase activity. Sampling and analysis of material from pregnant women was conducted in 2016–2018.Results. The reactivation of CMV in the first trimester of pregnancy led to an increase content in the phospholipase A2 in villous chorion by 2.5 times, by 1.5 times of fatty acid peroxides, 1.5 times arachidonic acid, palmitic acid by 1.3 times, number of trophoblast cells in a state of apoptosis by 4.7 times and decrease catalase activity by 1.44 times.Conclusion. As a result of the study, cytomegalovirus-dependent induction of oxidative stress and imbalance of fatty acids triggering apoptosis of trophoblast cells was identified. Increased apoptosis initiates inflammation and destructive processes in the early placenta.